From Glutinous‐Rice‐Inspired Adhesive Organohydrogels to Flexible Electronic Devices Toward Wearable Sensing, Power Supply, and Energy Storage. (1st October 2021) - Zhou, Hongwei; Lai, Jialiang; Zheng, Bohui; Jin, Xilang; Zhao, Guoxu; Liu, Hanbin; Chen, Weixing; Ma, Aijie; Li, Xusheng; Wu, Yuanpeng
Abstract: Flexible electronic devices (FEDs) based on hydrogels are attracting increasing interest, but the fabrication of hydrogels for FEDs with adhesiveness and high robustness in harsh‐temperature conditions and long‐term use remains a challenge. Herein, glutinous‐rice‐inspired adhesive organohydrogels are developed by introducing amylopectin into a copolymer network through a "one‐pot" crosslinking procedure in a glycerol–water mixed solvent containing potassium chloride as the conductive ingredient. The organohydrogels exhibit excellent transparency (>90%), conductivity, stretchability, tensile strength, adhesiveness, anti‐freezing property, and moisture retention ability. The wearable strain sensor assembled from the organohydrogels achieves a wide working range, high sensitivity (gauge factor: 8.82), low response time, and excellent reversibility, and properly responds in harsh‐temperature conditions and long‐time storage (90 days). The strain sensor is further integrated with a Bluetooth transmitter and receiver for fabricating wireless wearable sensors. Notably, a sandwich‐structured capacitive pressure sensor with organohydrogels containing reliefs as electrodes records a new gauge factor of 9.43 kPa −1 and achieves a wide response range, low detection limit, and outstanding reversibility. Furthermore, detachable and durable batteries and all‐in‐one supercapacitors are also fabricated utilizing the organohydrogels as electrolytes. Overall, this work offers a strategy to fabricate adhesive organohydrogels for robust FEDs toward wearable sensing, power supply, and energy storage. Abstract : Glutinous‐rice‐inspired organohydrogels with integrated adhesiveness, stretchability, transparency, conductivity, anti‐freezing, and moisture retention ability are developed by introducing amylopectin into a copolymer network and employed in flexible electronic devices toward wearable sensing, power supply, and energy storage. High sensitivity (gauge factor: = 8.82) for resistive strain sensors and a new sensitivity record (gauge factor: 9.43 kPa −1 )for hydrogel‐based pressure sensors are achieved.